Effectiveness, safety and utilization of vismodegib for locally advanced basal cell carcinoma under real-world conditions: non-interventional cohort study JONAS - Kaatz, Martin; Mohr, Peter; Livingstone, Elisabeth; Weichenthal, Michael; Kreuter, Alexander; Pföhler, Claudia; Leiter, Ulrike; Ulrich, Jens; Utikal, Jochen; Gutzmer, Ralf; Herbst, Rudolf; Schadendorf, Dirk (Acta dermato-venereologica, 2022)
Most patients with advanced basal cell carcinomas (BCCs) may not benefit sufficiently from standard treatment comprising surgery and radiation. Vismodegib, an oral selective hedgehog pathway inhibitor, is approved for treatment of patients with locally advanced BCC inappropriate for surgery or radiotherapy, or for patients with symptomatic metastatic BCC. In order to enhance understanding of the effectiveness, safety and utilization of vismodegib in clinical practice in Germany, a non-interventional study, JONAS, was conducted. A total of 53 patients with locally advanced BCC who initiated treatment with vismodegib between 2016 and 2018 were included in the study, which was embedded in the German ADOReg skin cancer registry. Duration of response, the primary endpoint, was 12.4 months, progression-free survival 32.2 months and overall response rate 77.4%. Most adverse events were mild to moderate. Overall, results confirmed previous findings, demonstrating favourable responses and manageable safety of vismodegib in patients with locally advanced BCC in clinical practice.